Waste no waste a storyboard for an animated video on proper Solid Waste Segregation - Doctura, Maria Regina P.
Proper solid waste management has been an issue in Davao City for years and thus an immediate action from the residents is needed. Information such as how-to-segregate-garbage is used to increase the procedural knowledge of the residents in Davao. Although important, this is not the most effective information for motivating the residents to segregate. Procedural information must be supplement with appropriate information that encourages residents to practice proper solid waste management. This type of information is impact knowledge ? and impact knowledge, such as environmental benefit, educates the residents as to why they have to segregate their garbage. Hence, the purpose of this study is to create a storyboard for an animated video that educates the residents about the environmental benefit of segregation. Using Edward Deci?sInstrinsic Motivation Theory and Anthony Friedmann?s Seven Step Method, a storyboard for an animated video is created to increase the interest of an individual to segregate. Exaggeration as a visual characteristic of animation is used in directing focus and retaining information. However, relying heavily on the visual aspect of video can produce misconceptions. Therefore voice-over, as a source of information, is also used to clearly convey the message of proper solid waste segregation